Clinical and immunological characteristics for BK polyomavirus-associated nephropathy after kidney transplantation - Siripoon T. (2023)
Introduction: BK polyomavirus (BKPyV)-associated nephropathy (BKPyVAN) can cause a significant risk of allograft impairment after kidney transplantation (KT). Intact BKPyV-specific immunity is associated with viral containment. This study investigated BKPyV-specific immunological factors among KT recipients. Methods: This prospective study in a single transplant center from January 2019 to August 2019 assessed associations between clinical and immunological characteristics, with a focus on BKPyV-cell-specific immunity and BKPyVAN, among KT recipients aged ≥15 years. The numbers of interferon-gamma (IFN-γ)-producing CD4+ T, CD8+ T, natural killer (NK), and natural killer T (NKT) cells were measured after stimulation with large T antigen and viral capsid protein 1 (VP1). Results: In total, 100 KT recipients were included (mean age ± SD, 42 ± 11 years); 35% of the recipients were female patients, and 70% had received induction immunosuppressive therapy. The 1-year cumulative incidence of high-level BKPyV DNAuria (possible BKPyVAN) and (presumptive BKPyVAN) was 18%. Among 40 patients with immunological factor data, pre-KT %NK cells (hazard ratio [HR], 1.258; 95% confidence interval [CI], 1.077–1.469; p =.004) and %VP1-specific NK cells (HR, 1.209; 95% CI, 1.055–1.386; p =.006) were factors independently associated with possible and presumptive BKPyVAN. KT recipients with possible and presumptive BKPyVAN were more likely to exhibit significant mean coefficients of %NK, %VP1-specific NK, and %NKT cells at 1 month after KT than before KT (all p <.05). Conclusion: Individuals with nonspecific and VP1-specific NK cells before KT and increasing numbers of these cells after KT may be at risk for high-level BKPyV DNAuria and presumptive BKPyVAN. Further studies are needed to determine the utility of BKPyV-specific innate immune surveillance in predicting the occurrence of BKPyVAN.